Energy based random repeat trust computation approach and Reliable Fuzzy and Heuristic Ant Colony mechanism for improving QoS in WSN. (November 2021) - Sakthidasan @ Sankaran, K.; Gao, Xiao-Zhi; Devabalaji, K.R.; Mohana Roopa, Y.
Abstract: The furthermost important issues in WSN are to provide a multi-path and multi-constraint Qualify of Service (QoS) routing for uninterrupted communications between the nodes. On one hand, multi-constrained QoS routing deals with identifying paths that assure numerous autonomous QoS limitations, and on the other hand, multi-path refers to the identification of multiple paths. The EB-RRTC (Energy based random repeat trust computation) algorithm is employed for encountering trusted nodes with destination node. The proposed method also employs the Reliable Fuzzy and Heuristic Concurrent ACO (RF-HEACO) QoS Routing Protocol to improve QoS. The HEACO-RF QoS Routing Protocol includes two phases. In the first phase, the Ant Colony Optimization algorithm is modified to identify a deposit of candidate routes among a pair of source and destination. While identifying the candidate routes along with the QoS metrics, heuristic factors and Reliable Fitness Functions are considered. In the second phase, the reliability technique is used to measure each path, and the paths with high reliability is selected by the ant agents using Fuzzy logic based on the metrics link stability, residual energy, and packet loss rate. Simulation outcomes prove that RF-HEACO QoS routing protocol can decrease the energy consumption and improve the packet delivery ratio, and packet loss rate with the minimum delay when compared with the techniques. In other words, our method is well capable of offering improved QoS (Quality of Service). Highlights: An energy based random repeat trust computation using Reliable Fuzzy and Heuristic Concurrent ACO is presented in this approach. The proposed method is capable of identifying the best and the most appropriate route proficiently to send messages to the destination node. For the trusted node classification, an approach of authentic node prediction by energy based random repeat trust computation is employed. The proposed technique is better in offering enhanced routing performance better QoS thereby tolerating delay in the network system. Simulation outcomes prove that RF-HEACOQoS routing protocol enhances the trust level of the node.